The effect of vehicle characteristics on road accidents - Jones, Ian Shore (Pergamon Press, 1976)
The Effect of Vehicle Characteristics on Road Accidents investigates whether vehicle characteristics related to handling and stability contribute to road accidents. Using multiple regression analysis, this book addresses driver and vehicle effects separately in order to define both the magnitude of the handling/accident causation problem as well as the relative importance of the various performance measures. This monograph is comprised of six chapters and begins with detailed studies of accidents to determine the circumstances which lead to loss of control or overturning of a car on the road,